Examination of Elite Physically Disabled Athletes' Motivation Levels of Participation in Sports - Yilmaz, A.; Gümüşay, A.; Akkaya, C.C. (Nevzat Demirci, 2021)
Determining which motivation source athletes have is important as it will ensure that correct and effective steps are taken to ensure success. The study focuses on examining the motivation of elite physically disabled athletes to participate in sports according to various variables. General survey model was used in the research. A total of 57 national athletes, including 16 arm wrestling, 13 swimming and 23 wheeled basketball athletes, participated in the study. The "Personal Information Form" developed by the researchers and the "Motivation of Participation in Sports for Persons with Disabilities Scale (MPSPDS)" developed by Demir et al. (2018) were used in the study. In the analysis of the data, besides descriptive statistics, Mann-Whitney U Test was used for paired comparisons and Kruskal Wallis H Test for multiple comparisons. In the findings obtained, it was found that there was a significant difference in motivation sources according to the variable of income and the second branch, but no significant difference was found according to the variables of gender, marital status, education level, branch, and time of disability. As a result, it was concluded that the physically disabled elite athletes, those who define their income level as medium in intrinsic and extrinsic motivations and those who have a secondary branch, have high motivation and show different characteristics from each other and cause them to be affected by different motivation sources. © Author(s) 2021 by the authors.
Keywords: Motivation; National Athlete; Participation In Sports; Physically Disabled; Sports